Horton hears a Who! - Seuss, Dr. (New York, Random House, 1982)
A city of Whos on a speck of dust are threatened with destruction until the smallest Who of all helps convince Horton's friends that Whos really exist.
Keywords: Stories in rhyme; Fantasy; Stories in rhyme